Does Good Corporate Governance and Political Connection have an Influence a Tax Avoidance? - Ni Luh Putu Agustin Nirmala Sari; Yusli Mariadi (Formosa Journal of Multidisciplinary Research, 2024)
The objective of this study is to examine the impact of institutional ownership, managerial ownership, independent commissioners, and political connections on tax avoidance within manufacturing companies listed on the Indonesia Stock Exchange between 2020 and 2022. Employing a purposive sampling method, 39 eligible companies were chosen for panel data regression analysis. The findings reveal that institutional ownership has a partially positive influence on tax avoidance, managerial ownership also has a partially positive impact on tax avoidance, independent commissioners exhibit a partially negative association with tax avoidance, and political connections have a partially positive effect on tax avoidance.